KESULITAN BELAJAR - Annisaa Dzakiyyah Syifaa; Ratu Ayu Magfiroh; Syafira Ramadhani; Tri Windi Oktara (Jurnal Riset Multidisiplin Edukasi, 2025)
The method used in this article is a literature review study which can be taken from various sources such as newspapers, magazines, the internet, books, documentation and journals. The purpose of this research is to find out what factors cause individuals to have difficulty learning and diagnose and resolve learning difficulties. Children who have learning beliefs have unique characteristics and different learning styles. Every child has the potential to achieve success in their studies. Learning fluency can be interpreted as a promise in the learning process, which in medical terms is often referred to as brain dysfunction. This article presents material regarding factors that influence individuals experiencing learning difficulties, diagnosis and resolution of learning difficulties experienced by individuals.